Eksistensi Budaya Ter-Ater : Implementasi Sumber Belajar Siswa Kelas IV di SDN Pakisan 01 Bondowoso - Dyah Ayu Puspitaningrum; Chumi Zahroul Fitriyah; Zetti Finali; Trapsila Siwi Hutami; Nora Sara Damayanti (Athallah Publishing Globalndo, 2026)
Tradisi